Sociodemographic Factors and Comorbidities Including Hyperparathyroidism Are Associated With an Increased Risk of Band Keratopathy: A Population-Based Study in Taiwan - Jan, Ren-Long; Wang, Jhi-Joung; Tseng, Sung-Huei; Chang, Yuh-Shin (Frontiers in Endocrinology, 2022)
Purpose: To investigate the association of comorbidities including hyperparathyroidism and sociodemographic factors with band keratopathy. Methods: This nationwide, population-based, retrospective, matched case-control study included 2,545 patients with band keratopathy identified from the Taiwan National Health Insurance Research Database based on the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code 371.43. The age-, sex-, and index date-matched control group included 15,270 non-band keratopathy controls selected from the Taiwan Longitudinal Health Insurance Database 2000. The associations of band keratopathy with sociodemographic conditions and comorbidities were examined using univariate logistic regression analyses, and paired t- tests were used for continuous variables. Adjusted logistic regression was used to compare the odds ratio (OR) for band keratopathy development. Results: Patients with hyperparathyroidism were more likely to develop band keratopathy than controls (OR, 43.5; 95% confidence interval [CI], 23.789–79.544; P < 0.001) even after conditional logistic regression (adjusted OR, 11.28; 95% CI, 5.461–23.33; P < 0.001). Other conditions that increased the odds of scleritis development included systemic diseases such as end-stage renal disease (ESRD) and diabetes mellitus (DM) and ocular conditions such as iridocyclitis, phthisis bulbi, and ever silicone oil retention. Regarding sociodemographic factors, >40% of patients with band keratopathy were aged ≥65 years old. Moreover, patients living in Eastern Taiwan and fishermen had higher odds of developing band keratopathy. Conclusions: Band keratopathy is significantly associated with hyperparathyroidism, ESRD, DM, iridocyclitis, phthisis bulbi, and ever silicone oil retention.